Factors Contributing to Rework and their Impact on Construction Projects Performance - Enshassi, Adnan; Sundermeier, Matthias; Abo Zeiter, Mohamed (International Journal of Sustainable Construction Engineering and Technology, 2017)
Rework is considered as a significant factor that influences the construction project performance in Palestine. Yet, little is known about its causes and possible impact, and therefore it remains an innate problem. The objective of this research is to identify the factors that contribute to rework and to investigate their possible impact on construction project performance. A set of 57 rework factors that categorized under seven groups were identified through an extensive literature review of previous studies and then were refined based on a pilot study. To elicit the views of professionals in the construction industry of the Gaza Strip about rework factors impact on construction project performance, 200 questionnaires were distributed and175 were returned. Data were analysed using descriptive analysis such as the Relative Importance Index (RII), mean, and Kruskall-Wallas test by employing SPSS version 17. The results of this research revealed that contractors’ related rework causes and human resources capability related rework causes are the major categories, which impact on the construction project performance. In addition, the findings showed that attempts to fraud, competitive pressure, ineffective management, schedule pressure and the absence of job security are the main rework factors, which have a considerable influence on construction project performance. The result of Kruskal-Wallis test indicated that there is an agreement among respondents with respect to the impact of rework causes on construction project performance. The findings may help construction partiesâ€™ in Gaza Strip to understand rework causes, which affect construction project performance. This will help in the derivation of appropriate strategies to reduce rework and hence, enable project performance improvements to be made. The recommendation of this study may also apply to other developing countries. The study contributes to the overall body of knowledge relevant to rework in the construction industry of developing countries. It draws attention to potential factors which contribute to rework on construction projects.Â